Palm Problems: Field and Laboratory Diagnosis - Monica L. Elliott; Timothy K. Broschat (EDIS)
PP-246, a 6-page illustrated fact sheet by Monica L. Elliott and Timothy K. Broschat, includes tips to determine when laboratory diagnostics may be useful and how to interpret and/or integrate field and laboratory diagnoses. Includes references. Published by the UF Department of Plant Pathology, June 2008.